A preparation method of low-foaming surfactant and cleaning agent

By using an embedded segment conjugate intermediate as a substrate in the surface active agent, the low bubble surfactant prepared by the demeterized amber -acid anhydride reaction solves the problem of excessive foam production and insufficient biodegradability, and realizes low bubbles. , The cleaning effect of strong pollution ability and high light transparency.

CN119019696BActive Publication Date: 2025-01-28GUANGDONG JUNHE TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411112392.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-01-28
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

Existing surfactants have the problem of excessive foam generation, which leads to waste and pollution of water resources. At the same time, their biodegradability and stability are insufficient, which affects the cleaning effect and the light transmittance of the glass.

Method used

The intermediate of the embedded segment co -vector is the base body, and the low -foam surfactant preparation prepared by the demeanide -based amine -based is the amber -acid anhydride reaction. By adjusting the molecular structure and branching response, it improves its turbidity and emulsification performance and reduce foam production.

Benefits of technology

The cleaning effect of low bubbles and strong pollution ability is achieved, the light transmission rate and the stability of the cleaning agent are improved, and the waste of water resources and pollution are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019696B_ABST
    Figure CN119019696B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surfactants, and in particular to a method for preparing a low-foam surfactant. A low-foam surfactant having a branched structure of polyisobutylene succinic anhydride containing a quaternary ammonium salt group grafted onto a long chain of a block copolymer is prepared. The low-foam surfactant effectively reduces the surface tension of an aqueous solution, has good wetting and foam suppression effects, strong emulsification ability, good decontamination and oil removal effects, and is easily biodegradable. The surfactant has good compatibility with other surfactants and auxiliary agents, so that the surfactant can replace traditional alkylphenol polyoxyethylene ether compounds to be prepared into a cleaning agent widely used in daily chemical cleaning and industrial cleaning of glass. The formed foam has a low height, does not contain phosphorus, does not contain strong alkali, and has a cleaning efficiency of more than 98%. The light transmittance of the glass after cleaning can be significantly improved, and the light transmittance of the cleaned glass reaches about 90%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of surfactants, in particular to a method for preparing a low-foaming surfactant. Background Art

[0002] Commonly used surfactants on the market include dodecyl polyoxyethylene ether, sodium dodecylbenzene sulfonate, nonylphenol polyoxyethylene ether, and sodium salts of fatty acids. These surfactants have high foaming properties and strong foam stability, which requires more rinsing times, not only wasting water resources, but also generating a large amount of wastewater, which has a very negative impact on water resources. Alkylphenol polyethers are the most toxic because they are metabolized into nonylphenol in the environment, which can cause damage to the body's oxygen free radicals and destroy lipids, affecting fish survival and threatening human health. Nonionic surfactants with branched structures have more excellent low-foaming properties, but their biodegradability is poor and they have certain irritation to the skin, resulting in limited applications.

[0003] Currently, the most common method for reducing foam is to add various defoamers. However, this approach often has numerous drawbacks. For example, the defoaming ability of defoamers decreases during use, ultimately leading to ineffective defoaming. This necessitates constant replenishment of defoamers to achieve consistent defoaming and foam suppression, leading to increased costs and impacting the stability of the production process due to varying levels of foam. Furthermore, various defoamers themselves have drawbacks, such as insensitivity to high temperatures, high alkalis, and shear forces. Excessive use of defoamers can also lead to phenomena such as "oil bleaching" and "emulsification." This requires the surfactant to possess excellent detergency properties while also being low-foaming and able to suppress the effects of oil-induced foaming. Balancing these functions is precisely the challenge. Most nonionic surfactants struggle to balance foaming and detergency, often resulting in reduced foam and decreased detergency. Therefore, the most fundamental approach to reducing foam is to develop low-foaming surfactants, thereby fundamentally addressing the foam problem. To meet the needs of low-foaming products, the development and application of low-foaming surfactants is crucial. The surfactants that have low foaming properties currently mainly include: EO (ethylene oxide) / PO (propylene oxide) block polyether, isooctyl phosphate derivatives, and polyether modified silicone surfactants.

[0004] Fatty alcohol polyoxyethylene ethers are used in various industries due to their excellent biodegradability and low irritation. However, literature has reported that PO polymerization chain forging in anionic surfactants can significantly increase the cross-sectional area of ​​surfactant molecules at the gas-liquid surface (Chen J, Hu XY, Fang Y, et al. Langmuir, 2019, 35, 3116-3125), and PO / EO mixed chain forging can further increase the cross-sectional area of ​​molecules at the gas-liquid surface (Forgiarini AM, Vejar F, Salager JL, et al. J Surfactants Deterg, 2010, 13(4): 451-458), that is, the number of molecules per unit area is reduced, thereby reducing the strength of the film and accelerating the defoaming speed. In theory, the molecular structure of this PO / EO mixed polymerization is not conducive to the generation of foam.

[0005] Chinese patent publication number CN104324655B discloses a low-foam polyether surfactant and its synthesis method. The low-foam polyether surfactant disclosed in the patent is an ethylene glycol block polyether with a molecular weight of 1800 to 4500. It uses ethylene glycol and ethylene oxide as the main raw materials, and the intermediate polyethylene glycol oligomer is formed by ring-opening copolymerization. It has low-foaming properties and good processing performance. It has excellent emulsification, dispersion and other cleaning properties. However, the PO / EO block polyether has a cloud point problem, which will cause the surfactant to precipitate in the cleaning agent, affecting the emulsification and dispersion properties of the cleaning agent. After precipitation, it easily adheres to the glass and is not easy to be cleaned off, which affects the light transmittance of the glass and thus affects the use of the glass. In addition, the glass is difficult to dry after cleaning, and is prone to the proliferation of mold and bacteria. White spots are also prone to appear after drying, affecting subsequent use.

[0006] Therefore, if we can combine the advantages of strong detergency of traditional surfactants and low foaming of polyether surfactants, while solving the shortcomings of each, we can invent a low-foaming surfactant that has a simple and easy synthesis process and good low-temperature fluidity, a high cloud point, strong emulsification ability, good permeability, and high cleaning efficiency. This is an urgent problem to be solved. Summary of the Invention

[0007] To overcome these shortcomings, the present invention aims to provide a low-foaming, environmentally friendly surfactant with low foaming properties and strong detergency. This surfactant, which has a molecular structure completely different from existing surfactants, effectively reduces the surface tension of aqueous solutions when dissolved in water, while also producing less foam. To achieve this objective, the present invention provides a low-foaming, environmentally friendly cleaning surfactant, which is produced by grafting aminated succinic anhydride onto a block copolymer intermediate.

[0008] Research has found that when using low-foaming polyether surfactants, which are block polyethers with a molecular weight of 2500-3500 and are formed by ring-opening copolymerization of propylene oxide and ethylene oxide as the main raw materials, although foaming can be reduced, cleaning efficiency is also reduced. Moreover, due to its inherent cloud point problem, the polyether surfactant will precipitate during use, affecting the emulsification and dispersion properties of the surfactant, ultimately affecting cleaning efficiency. After precipitation, it is easy to adhere to the glass and is difficult to clean off, which affects the light transmittance of the glass and thus affects its use. In addition, the glass is difficult to dry after cleaning and is prone to the proliferation of mold and bacteria. White spots are also prone to appear on the glass after drying, affecting the subsequent use of the glass.

[0009] Therefore, in order to solve the problem of low cleaning efficiency of low-foaming polyether surfactants caused by the low cloud point and the adhesion after precipitation, the low-foaming polyether surfactant is further modified to increase its cloud point and improve its emulsification performance. A low-foaming surfactant of the type grafted with aminated succinic anhydride using a block copolymer intermediate as a matrix is ​​prepared, specifically:

[0010] First, the preparation of the block copolymer intermediate is specifically as follows:

[0011] S001, in a reactor at a temperature of 90-140° C. and a reaction pressure of 0.15 MPa-0.35 MPa, under the protection of inert gas, using propylene glycol as an initiator and in the presence of a basic catalyst, propylene oxide is added dropwise to cause a polymerization reaction of the propylene oxide for 1-2 hours to obtain polypropylene glycol, and ethylene oxide is added dropwise to cause a reaction for 1-2 hours, and then ethylene oxide is added dropwise to cause a reaction for 3-4 hours to cause a polycondensation reaction between the polypropylene glycol and the ethylene oxide to obtain a block copolymer intermediate, which is designated as block copolymer intermediate A and has a molecular weight of 2500-3500;

[0012] S002, in a reaction kettle at a temperature of 50-60° C., reacting polyisobutylene succinic anhydride with 2-amino-2-methyl-1-propanol with stirring for 1-2 hours to obtain aminated polyisobutylene succinic anhydride;

[0013] S003, reacting the aminated polyisobutylene succinic anhydride and the block copolymer intermediate A at a reaction temperature of 80-90° C. for 5-8 hours to obtain a low-foaming surfactant based on the block copolymer A and grafted with the aminated polyisobutylene succinic anhydride.

[0014] The mass ratio of 2-amino-2-methyl-1-propanol to polyisobutylene succinic anhydride is 1:10-12; the mass ratio of aminated polyisobutylene succinic anhydride to block copolymer intermediate A is 1:5-6.

[0015] When a low-foaming surfactant based on a block copolymer and grafted with aminated polyisobutylene succinic anhydride was used in equal amounts to replace the block polyether surfactant, while maintaining the other ingredients unchanged, we found that this surfactant significantly improved the cloud point, virtually eliminating surfactant precipitation from the cleaning agent at room temperature. This significantly improved the emulsification and dispersibility of the cleaning agent, resulting in low foaming and easy drying of the cleaned glass. However, white spots still appeared after drying, and the cleaned glass was prone to fogging, ultimately affecting the glass's light transmittance. This is because the interior of the glass contains a large number of small cations, which have a high field strength. Within the glass, oxygen ions surround the cations, resulting in a balance of internal bond forces. However, strong surface forces exist on the surface due to residual bond forces. Consequently, the glass surface is easily corroded, especially in acidic, alkaline, water, and humid air conditions. This is largely due to the unique characteristics of its internal microstructure. Consequently, dust and oil stains are easily adsorbed on the glass surface. Once these dust and oil stains enter the glass interior, they are difficult to remove, resulting in irreversible chemical reactions that affect the glass's light transmittance.

[0016] Polyisobutylene succinic anhydride is a polymer with a molecular weight ranging from 200 to tens of thousands. Low-molecular-weight polyisobutylene succinic anhydride has good affinity to the glass surface, but is more susceptible to water vapor invasion; its hydrophilic base is too strong and cannot form a relatively stable film on the glass surface under water mist conditions, so it cannot have good anti-fog performance. High-molecular-weight polyisobutylene succinic anhydride has poor emulsification and wetting abilities, so it cannot be easily washed off after washing with water, and remains on the glass surface. After drying, it will form white spots, affecting the cleaning effect.

[0017] In order to further solve the above problems, we modified polyisobutylene succinic anhydride as follows:

[0018] S101, in a reactor at a temperature of 90-140° C. and a reaction pressure of 0.15 MPa-0.35 MPa, under inert gas protection, using propylene glycol as an initiator and in the presence of a basic catalyst, dropwise adding propylene oxide to polymerize the propylene oxide for 1-2 hours to obtain polypropylene glycol, and then dropwise adding ethylene oxide for 3-4 hours to polycondense the polypropylene glycol and ethylene oxide to obtain a block copolymer intermediate A having a molecular weight of 2500-3500;

[0019] S102, in a reaction kettle at a temperature of 50 to 60° C., stirring and reacting the polyisobutylene succinic anhydride mixture with 2-amino-2-methyl-1-propanol to obtain aminated polyisobutylene succinic anhydride;

[0020] The polyisobutylene succinic anhydride mixture is prepared by mixing polyisobutylene succinic anhydrides with molecular weights of 200 and 1000 in a mass ratio of 3:1;

[0021] Low molecular weight polyisobutenyl succinic anhydride has good water solubility and wetting ability, while high molecular weight polyisobutenyl succinic anhydride has good anti-foaming effect and emulsifying ability. After mutual matching, the mixture makes it easy to disperse, stable, and low-foaming. On the one hand, it can improve hydrophilicity and wettability, and quickly spread, disperse, and emulsify on the glass to achieve an efficient cleaning effect.

[0022] S103, N,N-dimethyldodecyl tertiary amine and concentrated hydrochloric acid are stirred at room temperature for 25-35 minutes, then anhydrous ethanol is added, followed by slowly adding dodecyltrimethylammonium chloride dropwise. The temperature is raised to 60°C, and the reaction is continued for 2-4 hours. After the reaction is complete, the ethanol is removed by vacuum distillation to obtain intermediate product B.

[0023] S104, laurylpropyldimethyl tertiary amine, is heated to 70°C and reacted with aminated polyisobutylene succinic anhydride for 4-5 hours. Intermediate product B and the block copolymer intermediate are then added, heated to 80-90°C, and stirred for 5-8 hours. This results in the grafting of two quaternary ammonium groups onto the polyisobutylene succinic anhydride. Furthermore, the polyisobutylene succinic anhydride containing quaternary ammonium groups is grafted onto the block copolymer intermediate A, forming a long block copolymer chain with branched chains of polyisobutylene succinic anhydride containing quaternary ammonium groups grafted onto it. This material is a novel low-foaming surfactant. The grafted side chains introduce a large number of hydrophilic groups, significantly improving the cloud point and hydrophilic properties of this low-foaming surfactant.

[0024] The mass ratio of the mixture of 2-amino-2-methyl-1-propanol and polyisobutylene succinic anhydride is 1:10-12; the mass ratio of N,N-dimethyldodecyl tertiary amine and dodecyltrimethylammonium chloride is 2:1; the mass ratio of dodecylpropyldimethyl tertiary amine, aminated polyisobutylene succinic anhydride, intermediate product B and block copolymer intermediate A is 1:(4-5):(1-3):(20-25); and the weight of concentrated sulfuric acid is 0.5-1.0‰ of the weight percentage of N,N-dimethyldodecyl tertiary amine.

[0025] Because the hydrophilic groups of these surfactant molecules carry a positive charge, they are able to interact electrostatically with surfaces. This novel low-foaming surfactant has two lipophilic groups: an isobutylene segment and a propylene oxide segment, and two hydrophilic groups: a quaternary ammonium salt segment and a maleic anhydride segment. Furthermore, it contains an amide group and an ethylene oxide segment, which not only enhance the synergistic interaction between the molecule and long-chain oils and improve emulsification, but also provide this low-foaming surfactant with anti-foaming properties, good surface activity, and excellent antibacterial properties.

[0026] From the perspective of improving light transmittance, it is speculated that the reason is that the modified polyisobutylene succinic anhydride has two hydrophilic groups at the same time, which can form a good bonding effect with the glass surface. On the other hand, its hydrophobic unit has strong hydrophobicity, has good repellency to fog, and is not easy to form fog. In addition, because the block copolymer intermediate A is grafted with the side-chain structure of polyisobutylene succinic anhydride with quaternary ammonium salt groups, the emulsification and wetting effect is enhanced, so that the polyether group will not be easily precipitated due to the increase in ambient temperature and adhere to the glass surface. Therefore, it can improve the cleaning efficiency and the light transmittance of the glass.

[0027] The reason this low-foaming surfactant can perform excellent cleaning on a macroscopic level is primarily due to its surface activity, which reduces the surface tension of liquids, and its solubilizing effect, which promotes the dissolution of insoluble substances. The essence of foam is a bilayer formed when the hydrophilic groups of two layers of surfactant molecules are close together, while the lipophilic groups are in the air. This makes it easy for foam to form in large air-rich environments such as showers. However, how to make the formed foam burst quickly is crucial. When the rate of foam generation is slower than the rate of foam burst, low-foaming properties are manifested on a macroscopic scale. Therefore, choosing the appropriate ratio of hydrophilic and lipophilic groups is the key to controlling the rate of foam generation and burst, achieving excellent low-foaming and anti-foaming properties.

[0028] Therefore, when the polyether is a block copolymer of EO (ethylene oxide) and PO (propylene oxide) with a number-average molecular weight of 2500-3500, a high EO content (i.e., an EO molar content of 50% or more) is selected for improved water solubility and wettability. However, this results in relatively weak anti-foaming properties. Conversely, a low EO content will enhance anti-foaming properties but will also result in a lower cloud point. This is because the cloud point is closely related to the number of ethylene oxide units in the molecule. A lower EO content means fewer ethylene oxide units, which reduces the molecule's hydrophilicity, lowering the cloud point and increasing viscosity, surface tension, and emulsification properties. The lower the cloud point, the greater the amount of precipitate, making it more likely to accumulate on the glass surface. Increased surface tension reduces surface activity and emulsification properties, further exacerbating cleaning efficiency, ultimately resulting in poor cleaning results and reduced light transmittance. However, increasing the EO content increases the cloud point and surface tension, but also increases viscosity. This results in very fine, less easily broken foam, which dramatically increases the amount of foam formed. This increased foaming, in turn, leads to a host of other problems. Therefore, balancing the EO content is crucial. Therefore, the EO molar content is controlled below 50%, and the cloud point is raised by grafting other hydrophilic groups. Therefore, the mass ratio of ethylene oxide to propylene oxide is 1:3-5, and the mass ratio of propylene glycol to propylene oxide is 1:1.

[0029] During the cleaning process, low-foaming surfactants first penetrate impurity particles and continuously diffuse through them, further swelling, softening, and loosening them. When the surfactant concentration in the cleaning solution exceeds the critical micelle concentration, impurity particles are solubilized to varying degrees, rapidly removing a large amount of contaminants. Furthermore, under mechanical forces, contaminants on the glass surface are emulsified by the surfactants in the cleaning solution. These forces, or the action of certain water-soluble polymers, disperse and suspend the contaminants in the aqueous solution. Under the influence of hydrophobic driving forces, the contaminants are then adsorbed or accumulated at the oil-water interface. Therefore, the entire cleaning process is synergistically accomplished through the wetting, penetration, and emulsification effects of low-foaming surfactants. After the long-chain alkyl tertiary amine is grafted through the quaternization reaction, on the one hand, the strong adsorption and film-forming properties of the cationic group can act quickly on the glass surface, accelerating the penetration, and its hydrophilic group can be inserted between the quaternary ammonium groups on the micelle surface, thereby reducing the electrostatic repulsion between the quaternary ammonium groups; on the other hand, intermolecular hydrogen bonds can be formed between the surfactant molecules, which promotes the micellization process and significantly reduces the surface tension, thereby improving the speed and efficiency of the entire cleaning process.

[0030] On the other hand, cationic groups also have excellent antibacterial properties. Compared with small-molecule surfactants, they have the following advantages: because their molecular structure contains more quaternary ammonium salt groups, they can form a more stable antibacterial film, forming a strong affinity with the cell membrane of bacteria, making it last longer on the surface and having a lasting bactericidal effect. More importantly, they have good biodegradability and low toxicity, and will not cause pollution or harm to the environment or the human body. Therefore, a low-foaming surfactant with a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of a block copolymer prepared effectively solves the white spots and light transmittance problems that occur after glass cleaning, and can also have a certain bactericidal effect, providing a good environment for subsequent glass use.

[0031] The present invention also aims to provide a cleaning agent that can effectively reduce the surface tension of aqueous solutions, forms low-height foam, contains no phosphorus or strong alkali, and can achieve excellent cleaning results when cleaning glass. The cleaning agent comprises the following raw materials and their weight percentages: 15-20 parts low-foaming surfactant, 2-3 parts polyoxyethylene polyoxypropylene isooctanol ether, 3-5 parts glycerin, 2-5 parts polyethylene glycol, 1-2 parts sodium metasilicate, 1-2 parts sodium polyaspartate, and 50-70 parts water.

[0032] The alkanolamides include coconut oil diethanolamide, coconut oil monoethanolamide, lauric acid diethanolamide, and lauric acid monoisopropanolamide; the isooctyl alcohol polyoxyethylene polyoxypropylene ether includes at least one of EH-6 and EH-9.

[0033] Furthermore, sodium polyaspartate was selected as an auxiliary agent. It is a phosphorus-free, green, and friendly chelating agent. In cleaning agents, it not only exhibits excellent integration and dispersion, hydrophilicity, but also good biocompatibility and degradability. It also significantly enhances the detergent's detergency. Due to its peptide bond and carboxyl groups, it possesses exceptional integration, adsorption, and dispersion capabilities, as well as low foaming properties.

[0034] Furthermore, a method for preparing a cleaning agent is provided, specifically comprising:

[0035] The raw materials are weighed according to the above mass parts and mixed to obtain the cleaning agent. The cleaning agent is a low-foaming, biodegradable and highly efficient cleaning agent for cleaning glass.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The low-foam surfactant designed and synthesized by the present application is a low-foam surfactant that adopts a PO / EO block copolymer intermediate as a matrix on the molecular structure and is grafted with aminated succinic anhydride, which solves the problem of surfactant precipitation caused by the low cloud point of the block copolymer, and the problem of high adhesiveness and reduced emulsifying ability. In addition, a low-foam surfactant is provided, which is a low-foam surfactant having a branched structure of polyisobutylene succinic anhydride containing a quaternary ammonium salt group grafted on the long chain of the block copolymer. The low-foam surfactant of this novel structure has an lipophilic group and an isobutylene segment and a propylene oxide segment, and a hydrophilic group is a quaternary ammonium salt and a maleic anhydride segment. In addition, it also contains an amide group and an ethylene oxide segment. The combined effect of these active functional groups not only solves the cloud point problem, but also helps improve the molecular cross-sectional area of ​​the molecule on the interface, reduces the interfacial film strength, reduces surface tension, reduces the foam stability of the surfactant, improves the speed of foam breakdown, and helps strengthen the synergistic ability with the long chain, strengthens emulsifying power, and improves cleaning efficiency. This low-foam surfactant has foam suppression, low foaming property and good surface activity, and good antibacterial properties.

[0038] 2) The low-foaming surfactant prepared by the present invention, through compounding with other raw materials, synergistically acts to achieve excellent oil emulsification and penetration, facilitate rinsing, and form an adsorption film on the glass surface during cleaning, thereby increasing the surface transmittance of the glass. Furthermore, the cleaned glass surface exhibits excellent anti-fog properties. This type of surfactant also contains no toxic or harmful ingredients, is environmentally friendly, and is biodegradable.

[0039] 3) The present invention discloses a low-foaming surfactant having a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of a block copolymer. The synthesis method is simple, easy to operate, and has low production cost. When dissolved in water, the low-foaming surfactant effectively reduces the surface tension of the aqueous solution, forms minimal foam, and has a cleaning efficiency exceeding 98%, demonstrating excellent cleaning effectiveness and being highly suitable for cleaning various glass surfaces. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 , a graph showing the cleaning efficiency of Example 2 and Comparative Example 1-2 versus cleaning time DETAILED DESCRIPTION

[0041] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0042] Example 1

[0043] To prepare a low-foaming surfactant, first, a block copolymer intermediate A is prepared, specifically:

[0044] S001, in a reactor at a temperature of 100° C. and a reaction pressure of 0.15 MPa, under nitrogen protection, 500 parts of propylene glycol as an initiator, in the presence of 0.1 parts of sodium hydroxide as a catalyst, 400 parts of propylene oxide are added dropwise to polymerize the propylene oxide for 2 hours to obtain polypropylene glycol, 100 parts of propylene oxide are added dropwise to react for 1 hour, and then 100 parts of ethylene oxide are added dropwise to polycondense the polypropylene glycol with the ethylene oxide for 3 hours to obtain a block copolymer intermediate A having an average molecular weight of 3471 and a molar content of EO segment: PO segment of 1:5;

[0045] A low-foaming surfactant based on the block copolymer intermediate A and grafted with aminated polyisobutylene succinic anhydride is prepared, specifically:

[0046] S002, in a reaction kettle at a temperature of 60° C., stirring and reacting 100 parts of polyisobutylene succinic anhydride with a molecular weight of 2000 and 10 parts of 2-amino-2-methyl-1-propanol to obtain aminated polyisobutylene succinic anhydride;

[0047] S003, reacting 50 parts of aminated polyisobutylene succinic anhydride with 250 parts of a block copolymer intermediate at a reaction temperature of 70° C. for 8 hours to obtain a low-foaming surfactant based on the block copolymer and grafted with aminated polyisobutylene succinic anhydride.

[0048] Then, the low-foaming surfactant was used to prepare a cleaning agent, which included the following raw materials and their weight parts: 15 parts of low-foaming surfactant, 6 parts of EH-6, 4 parts of lauric acid diethanolamide, 5 parts of glycerol, 3 parts of polyethylene glycol, 1 part of sodium metasilicate, 2 parts of sodium polyaspartate, and 50 parts of water;

[0049] Weigh the raw materials according to the above mass parts, stir at 40°C for 2 hours, mix evenly and filter to prepare the cleaning agent.

[0050] Example 2

[0051] First, a low-foaming surfactant is prepared, that is, a low-foaming surfactant having a branched structure of polyisobutylene succinic anhydride containing a quaternary ammonium salt group grafted onto the long chain of a block copolymer. The preparation method is as follows:

[0052] S101, in a reactor at a temperature of 100° C. and a reaction pressure of 0.15 MPa, under nitrogen protection, 500 parts of propylene glycol as an initiator and 0.1 parts of sodium hydroxide as a catalyst are dropwise added to polymerize the propylene oxide for 2 hours to obtain polypropylene glycol, 100 parts of propylene oxide are further dropwise added to react for 1 hour, and 100 parts of ethylene oxide are further dropwise added to polycondense the polypropylene glycol with the ethylene oxide for 3 hours to obtain a block copolymer intermediate A having an average molecular weight of 3419 and a molar content of EO segment:molar content of PO segment of 1:5;

[0053] S102, in a reactor at a temperature of 60° C., mixing polyisobutylene succinic anhydride with a molecular weight of 200 and polyisobutylene succinic anhydride with a molecular weight of 1000 in a mass ratio of 3:1 to obtain a mixture of polyisobutylene succinic anhydride, and reacting 100 parts of the mixture of polyisobutylene succinic anhydride with 10 parts of 2-amino-2-methyl-1-propanol with stirring to obtain aminated polyisobutylene succinic anhydride;

[0054] S103, 100 parts of N,N-dimethyldodecyl tertiary amine and 0.1 parts of concentrated hydrochloric acid were stirred at room temperature for 35 minutes, 100 parts of anhydrous ethanol were added, 50 parts of dodecyltrimethylammonium chloride were slowly added dropwise, the temperature was raised to 60° C., and the reaction was carried out for 3 hours. After the reaction was completed, the ethanol was removed by distillation under reduced pressure to obtain an intermediate product B;

[0055] S104, 10 parts of laurylpropyldimethyl tertiary amine are heated to 70°C and reacted with 50 parts of aminated polyisobutylene succinic anhydride for 4 hours, then 10 parts of intermediate product B and 250 parts of block copolymer intermediate are added, the temperature is raised to 80°C, and the reaction is stirred for 8 hours to graft two quaternary ammonium salt groups onto the polyisobutylene succinic anhydride, and the polyisobutylene succinic anhydride containing quaternary ammonium salt groups is grafted onto the block copolymer intermediate to form a low-foaming surfactant with a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of the block copolymer.

[0056] Then, a cleaning agent is prepared using the low-foaming surfactant, comprising the following raw materials and their weight parts: 15 parts of low-foaming surfactant, 6 parts of EH-6, 4 parts of lauric acid diethanolamide, 5 parts of glycerol, 3 parts of polyethylene glycol 400, 1 part of sodium metasilicate, 2 parts of sodium polyaspartate, and 50 parts of water;

[0057] Weigh the raw materials according to the above mass parts, stir at 40°C for 2 hours, mix evenly and filter to prepare the cleaning agent.

[0058] Example 3

[0059] A low-foaming surfactant is prepared, namely a low-foaming surfactant having a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of a block copolymer. The preparation method is as follows:

[0060] S101, in a reactor at a temperature of 100° C. and a reaction pressure of 0.15 MPa, under nitrogen protection, 400 parts of propylene glycol as an initiator and 0.1 parts of sodium hydroxide as a catalyst are added dropwise to cause a polymerization reaction of the propylene oxide for 2 hours to obtain polypropylene glycol, 100 parts of propylene oxide are added dropwise to cause a reaction for 1 hour, and then 100 parts of ethylene oxide are added dropwise to cause a condensation reaction between the polypropylene glycol and the ethylene oxide for 3 hours to obtain a block copolymer intermediate A having an average molecular weight of 3047 and a molar content of EO segment:molar content of PO segment of 1:4;

[0061] S102, in a reactor at 60° C., mixing polyisobutylene succinic anhydride with a molecular weight of 200 and polyisobutylene succinic anhydride with a molecular weight of 1000 in a mass ratio of 3:1 to obtain a mixture of polyisobutylene succinic anhydride, and reacting 100 parts of the mixture of polyisobutylene succinic anhydride with 12 parts of 2-amino-2-methyl-1-propanol with stirring to obtain aminated polyisobutylene succinic anhydride;

[0062] S103, 100 parts of N,N-dimethyldodecyl tertiary amine and 0.1 parts of concentrated hydrochloric acid were stirred at room temperature for 25 minutes, 100 parts of anhydrous ethanol were added, and 50 parts of dodecyltrimethylammonium chloride were slowly added dropwise. The temperature was raised to 60° C. and the reaction was carried out for 4 hours. After the reaction was completed, the ethanol was removed by distillation under reduced pressure to obtain an intermediate product B;

[0063] S104, 10 parts of laurylpropyldimethyl tertiary amine are heated to 70°C and reacted with 50 parts of aminated polyisobutylene succinic anhydride for 5 hours, then 20 parts of intermediate product B and 230 parts of block copolymer intermediate are added, the temperature is raised to 80°C, and the mixture is stirred and reacted for 5 hours to graft two quaternary ammonium groups onto the polyisobutylene succinic anhydride, and the polyisobutylene succinic anhydride containing quaternary ammonium groups is grafted onto the block copolymer intermediate, forming a low-foaming surfactant with a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium groups grafted onto the long chain of the block copolymer.

[0064] Then, the low-foaming surfactant is used to prepare a cleaning agent, which includes the following raw materials and their weight parts: 20 parts of low-foaming surfactant, 3 parts of EH-9, 3 parts of coconut oil diethanolamide, 3 parts of glycerin, 5 parts of polyethylene glycol 400, 2 parts of sodium metasilicate, 2 parts of sodium polyaspartate, and 60 parts of water;

[0065] Weigh the raw materials according to the above mass parts, stir at 40°C for 2 hours, mix evenly and filter to prepare the cleaning agent.

[0066] Example 4

[0067] A low-foaming surfactant is prepared, namely a low-foaming surfactant having a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of a block copolymer. The preparation method is as follows:

[0068] S101, in a reactor at a temperature of 100° C. and a reaction pressure of 0.15 MPa, under nitrogen protection, using 300 parts of propylene glycol as an initiator and 0.1 parts of sodium hydroxide as a catalyst, 200 parts of propylene oxide are dropwise added to polymerize the propylene oxide for 2 hours to obtain polypropylene glycol, 100 parts of propylene oxide are further dropwise added to react for 1 hour, and then 100 parts of ethylene oxide are dropwise added to polycondense the polypropylene glycol with the ethylene oxide for 3 hours to obtain a block copolymer intermediate A having an average molecular weight of 2626; and a molar content of the EO segment: the molar content of the PO segment is 1:3;

[0069] S102, in a reactor at 60° C., mixing polyisobutylene succinic anhydride with a molecular weight of 200 and polyisobutylene succinic anhydride with a molecular weight of 1000 in a mass ratio of 3:1 to obtain a mixture of polyisobutylene succinic anhydride, and reacting 100 parts of the mixture of polyisobutylene succinic anhydride with 11 parts of 2-amino-2-methyl-1-propanol with stirring to obtain aminated polyisobutylene succinic anhydride;

[0070] S103, 100 parts of N,N-dimethyldodecyl tertiary amine and 0.1 parts of concentrated hydrochloric acid were stirred at room temperature for 30 minutes, 100 parts of anhydrous ethanol were added, 50 parts of dodecyltrimethylammonium chloride were slowly added dropwise, the temperature was raised to 60° C., and the reaction was carried out for 3 hours. After the reaction was completed, the ethanol was removed by distillation under reduced pressure to obtain an intermediate product B;

[0071] S104, 10 parts of laurylpropyldimethyl tertiary amine are heated to 70°C and reacted with 50 parts of aminated polyisobutylene succinic anhydride for 5 hours, then 10 parts of intermediate product B and 240 parts of block copolymer intermediate are added, the temperature is raised to 80°C, and the reaction is stirred for 8 hours to graft two quaternary ammonium salt groups onto the polyisobutylene succinic anhydride, and the polyisobutylene succinic anhydride containing quaternary ammonium salt groups is grafted onto the block copolymer intermediate, forming a low-foaming surfactant with a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of the block copolymer.

[0072] Then, a cleaning agent is prepared using the low-foaming surfactant, comprising the following raw materials and their weight parts: 18 parts of low-foaming surfactant, 5 parts of EH-6, 5 parts of lauric acid diethanolamide, 3 parts of glycerol, 2 parts of polyethylene glycol 400, 1 part of sodium metasilicate, 1 part of sodium polyaspartate, and 70 parts of water;

[0073] Weigh the raw materials according to the above mass parts, stir at 40°C for 2 hours, mix evenly and filter to prepare the cleaning agent.

[0074] Comparative Example 1 does not contain the low-foaming surfactant prepared in the present invention, but uses an equal amount of EH-6 instead; the rest is the same as Example 2;

[0075] Comparative Example 2: The low-foaming surfactant was replaced by an equal amount of the low-foaming polyether surfactant prepared in Example 4 of CN104324655B, and the rest was the same as in Example 2;

[0076] Comparative Example 3, the low-foaming surfactant was replaced by an equal amount of a commercially available conventional cleaning surfactant - alkylphenol polyoxyethylene ether NP-10, and the rest was the same as in Example 2;

[0077] Comparative data of experimental effects

[0078] 1. Surfactant cloud point test and surface tension test results

[0079] According to the national standard GB / T5559-2010 for the determination of the cloud point of ethylene oxide-type and ethylene oxide-propylene oxide block polymer nonionic surfactants, the low-foaming surfactants prepared in Examples 1-4 and the surfactants involved in Comparative Examples 1-3 were treated, placed in a sealed glass container, and heated. The temperature at which the appearance of the cleaning agent became turbid was recorded and recorded as the cloud point. See Table 1 for details.

[0080] The surface tension of the surfactants involved in Examples 1-4 and Comparative Examples 1-3 was measured using a JHZL fully automatic surface tension meter (Yangzhou Junhao Electric Co., Ltd.), as shown in Table 1.

[0081] The appearance and stability of the surfactants involved in Examples 1-4 and Comparative Examples 1-3 were tested. The stability test was performed after the surfactants were placed in an oven at 55°C for 48 hours and then returned to room temperature. See Table 1 for details.

[0082] Table 1 Performance test of surfactants

[0083]

[0084] As can be seen from Table 1, the cloud point of the low-foaming surfactant of Example 1, which is based on block copolymer intermediate A and grafted with aminated polyisobutylene succinic anhydride, is higher than that of the surfactants of Comparative Examples 1-2. However, because its cloud point is only 56°C, its high-temperature stability is somewhat lacking. Therefore, during cleaning, slight precipitation and turbidity may occur, resulting in reduced cleaning efficiency. The low-foaming surfactants of Examples 2-3, which further improve the polyisobutylene succinic anhydride to obtain a low-foaming surfactant with a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of the block copolymer, significantly increase the cloud point, promote its dissolution rate in the solvent, accelerate cleaning efficiency, and achieve more thorough cleaning.

[0085] 2. Test results of cleaning efficiency and light transmittance

[0086] For ordinary glass test pieces, the oily components include typical dirt such as grease, syrup, dust, pigment and protein. The specific composition is: 20.0g liquid paraffin, 20.0g soy sauce, 20.0g cooking oil, 20.0g mud, 20.0g brown sugar syrup. Among them, the mud was taken from ordinary yellow soil and was pretreated before the experiment, that is, it was dried to constant weight in a (55±2)℃ constant temperature drying oven and passed through an 80-mesh sieve. The specific steps for preparing the glass test piece are as follows: take a clean glass piece, evenly apply the prepared oily dirt, and place it flat on a clean enamel tray, then place it in a (55±2)℃ constant temperature drying oven for 10 hours, take it out, and cool and age it in a desiccator for 2 hours.

[0087] Transmittance measurement: Place the glass test piece in a V-1200 UV-Vis spectrophotometer, select air as the reference, and set the measurement wavelength range to 400-750nm. Measure the transmittance of the glass test piece before and after cleaning.

[0088] The mass method is used to characterize the cleaning ability of the cleaning agent. A glass specimen coated with oil is cleaned with the prepared cleaning agent, taken out, dried, and weighed. The cleaning efficiency is calculated according to the following formula.

[0089] Cleaning efficiency = (C0-C) / C0×100%

[0090] Where C0 is the sum of the mass of the glass piece and the weight of the oil stain, in g;

[0091] C is the weight after cleaning, in g;

[0092] The cleaning agents of Examples 1-4 and Comparative Examples 1-3 were respectively prepared into aqueous solutions with a mass fraction of 2%, and used to spray clean glass test pieces evenly smeared with oil stains. The cleaning efficiency of the cleaning agents of Examples 1-4 and Comparative Examples 1-3 was calculated and shown in Table 2. At the same time, a cleaning efficiency curve of Example 2 and Comparative Examples 1 and 2 was drawn as a function of time at a temperature of 50°C, as shown in Table 2. Figure 1 The light transmittance of the cleaned glass specimens was measured. The light transmittance results of the cleaned glass are shown in Table 2.

[0093] Because the cleaning efficiency is also related to temperature, the cleaning efficiency at 25℃, 50℃ and 70℃ with a cleaning time of 5 minutes was tested, and the corresponding light transmittance of the cleaned glass test pieces was measured, see Table 2;

[0094] Table 2 Cleaning efficiency and light transmittance

[0095]

[0096] As can be seen from Table 2, the cleaning efficiency of Examples 1-4 and Comparative Examples 1-3 increases with increasing temperature, while the cleaning efficiency of Examples 2-4 does not change much with temperature. They have excellent cleaning efficiency at both low and high temperatures, and the cleaning efficiency is above 98%. Figure 1It can also be seen that the cleaning efficiency of Example 2 reaches over 95% in just 3 minutes. This is because the low-foaming surfactant with a branched structure has strong emulsifying ability and good penetration and dispersibility, making it easy to decompose and remove oil stains on the glass. Furthermore, the light transmittance of the glass in Examples 2-4 is very good when the temperature is increased from 25°C to 70°C, and it also increases slightly with increasing temperature, basically approaching the maximum light transmittance of ordinary glass. This is simply because the low-foaming surfactant used in Example 2, which has a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium groups grafted onto the long chains of a block copolymer prepared by the present invention, contains not only a large number of hydrophilic groups but also a large number of lipophilic groups, making it very effective in cleaning both hydrophilic and lipophilic substances on the glass, thus achieving excellent cleaning results at different temperatures. In contrast, the low-foaming surfactant used in Example 1 has a cloud point of 56°C and therefore precipitates as the temperature rises. However, the surfactant, based on the block copolymer intermediate, has strong adhesion and easily absorbs and penetrates the glass surface, causing a decrease in light transmittance. The surfactants in Comparative Examples 1-2 have lower cloud points, resulting in the precipitation of more adhesive substances, further reducing transparency. Comparative Example 3 uses a surfactant with a higher cloud point, and because surfactants like NP-10 significantly enhance their emulsification ability at high temperatures, it exhibits excellent cleaning performance at high temperatures. However, the high temperature generation of a large amount of fine foam can somewhat affect the cleaning effect.

[0097] 3. Overall performance test of cleaning agent

[0098] The cleaning agents of Examples 1-4 and Comparative Examples 1-3 were respectively prepared into 2% by mass aqueous solutions. The foam height of the solutions after circulation for 30 minutes at 25°C was measured using a foam meter with a 1000 ml graduated cylinder and a circulation pump, as shown in Table 3. The foam stability refers to the foam height in the graduated cylinder after the foam meter stops circulating and remains stationary for 2 minutes, as shown in Table 3.

[0099] The biodegradability of the nonionic surfactants in the above examples was determined according to the test method for biodegradability of surfactants (GB / T 15818-2006). See Table 3.

[0100] Table 3 Performance test of surfactants

[0101] Sample Appearance of 2% aqueous solution Foaming Antifoaming properties Biodegradability Example 1 Clarity and transparency 30ml / 30min 5ml 95 Example 2 Clarity and transparency 10ml / 30min 0ml 96 Example 3 Clarity and transparency 14ml / 30min 0ml 97 Example 4 Clarity and transparency 19ml / 30min 2ml 96 Comparative Example 1 Clarity and transparency 108ml / 30min 38ml 96 Comparative Example 2 Clarity and transparency 187ml / 30min 65ml 98 Comparative Example 3 Clarity and transparency 581ml / 30min 189ml 68

[0102] In general, surface tension is lower, and the work that the foam of generating same total surface area needs to do is less, and the foaming ability of surfactant is stronger. In addition, the stability of foam is mainly relevant with the intensity of interfacial adsorption film. The hydrophobic interaction between surfactant is stronger, and the adsorption on the adsorption film surface is tighter, and the intensity of the surface adsorption film is also large, so that foam is more stable. As shown in Table 3, under the same conditions, the foam suppression performance of the foam of embodiment 2-4 is better. This is because the asymmetry of the molecular structure of the low-foam surfactant used is maximum, and the branched structure of the polyisobutylene succinic anhydride containing quaternary ammonium salt group has been grafted, and the intermolecular interaction is the strongest, therefore tighter on interfacial adsorption film, the joint action of hydrophilic group and lipophilic group reaches good low-foam foam suppression performance, not only makes foam generation less, and what produces is all big foam, and solution breaks, therefore can eliminate rapidly after circulation stops.

[0103] From the above test data, it can be seen that the low-foaming surfactants in Examples 2-4 not only have a high cloud point and good cleaning performance, but also have excellent low-foaming performance and biodegradability.

[0104] The above description is only used to illustrate the technical solution of the present invention and is not intended to limit it. Any modifications and changes made to the technical solution of the present invention by ordinary persons in the art shall still fall within the scope of the present invention as long as they do not depart from the overall concept of the present invention.

Claims

1. A method for preparing a low-foaming surfactant, characterized in that: The low-foaming surfactant is a low-foaming surfactant composed of a block copolymer intermediate A as a matrix and grafted with aminated succinic anhydride; Wherein, the preparation of block copolymer intermediate A is specifically as follows: S001, in a reactor at a temperature of 90 to 140° C. and a reaction pressure of 0.15 MPa to 0.35 MPa, under the protection of inert gas, propylene glycol is used as an initiator, propylene oxide is added dropwise in the presence of an alkaline catalyst to polymerize propylene oxide for 1 to 2 hours to obtain polypropylene glycol, propylene oxide is added dropwise for 1 to 2 hours, and then ethylene oxide is added dropwise for 3 to 4 hours to cause polycondensation of polypropylene glycol and ethylene oxide to obtain a block copolymer intermediate A having a molecular weight of 2500-3500; S002, in a reaction kettle at a temperature of 50-60° C., reacting polyisobutylene succinic anhydride with 2-amino-2-methyl-1-propanol with stirring to obtain aminated polyisobutylene succinic anhydride; S003, reacting the aminated polyisobutylene succinic anhydride and the block copolymer intermediate A for 5 to 8 hours at a reaction temperature of 80 to 90° C. to obtain a low-foaming surfactant having the block copolymer intermediate A as a matrix and grafted with the aminated polyisobutylene succinic anhydride; The mass ratio of 2-amino-2-methyl-1-propanol to polyisobutylene succinic anhydride is 1:10-12; the mass ratio of aminated polyisobutylene succinic anhydride to block copolymer intermediate A is 1:5-6.

2. The method for preparing a low-foaming surfactant according to claim 1, characterized in that: The low-foaming surfactant is a surfactant further modified on the basis of the low-foaming surfactant in claim 1, specifically a low-foaming surfactant having a branched structure of polyisobutylene succinic anhydride containing quaternary ammonium salt groups grafted onto the long chain of a block copolymer, and the preparation method thereof is as follows: S101, in a reactor at a temperature of 90 to 140° C. and a reaction pressure of 0.15 MPa to 0.35 MPa, under the protection of an inert gas, using propylene glycol as an initiator, in the presence of an alkaline catalyst, propylene oxide is added dropwise to polymerize the propylene oxide for 1 to 2 hours to obtain polypropylene glycol, propylene oxide is added dropwise to react for 1 to 2 hours, and then ethylene oxide is added dropwise to react for 3 to 4 hours to cause polycondensation of the polypropylene glycol and ethylene oxide to obtain a block copolymer intermediate A having a molecular weight of 2500 to 3500; S102, in a reaction kettle at a temperature of 50 to 60° C., reacting the polyisobutylene succinic anhydride mixture with 2-amino-2-methyl-1-propanol with stirring to obtain aminated polyisobutylene succinic anhydride; S103, N,N-dimethyldodecyl tertiary amine and concentrated hydrochloric acid are stirred at room temperature for 25 to 35 minutes, anhydrous ethanol is added, dodecyl trimethyl ammonium chloride is slowly added dropwise, the temperature is raised to 60° C. and reacted for 2 to 4 hours. After the reaction is completed, ethanol is removed by reduced pressure distillation to obtain an intermediate product B; S104, dodecylpropyl dimethyl tertiary amine, is heated to 70°C and reacted with aminated polyisobutylene succinic anhydride for 4 to 5 hours, then the intermediate product B and the block copolymer intermediate A are added, the temperature is raised to 80 to 90°C, and the reaction is stirred for 5 to 8 hours to graft the two quaternary ammonium salt groups onto the polyisobutylene succinic anhydride, and the polyisobutylene succinic anhydride containing the quaternary ammonium salt group is grafted onto the block copolymer intermediate to form a low-foaming surfactant with a branched structure of polyisobutylene succinic anhydride containing the quaternary ammonium salt group grafted onto the long chain of the block copolymer.

3. The method for preparing a low-foaming surfactant according to claim 2, characterized in that: in, The polyisobutylene succinic anhydride mixture is prepared by mixing polyisobutylene succinic anhydrides with molecular weights of 200 and 1000 in a mass ratio of 3:1; The mass ratio of the mixture of 2-amino-2-methyl-1-propanol and polyisobutylene succinic anhydride is 1:10-12; the mass ratio of N,N-dimethyldodecyl tertiary amine and dodecyl trimethyl ammonium chloride is 2:1; The mass ratio of dodecylpropyldimethyl tertiary amine, aminated polyisobutylene succinic anhydride, intermediate product B and block copolymer intermediate A is 1:(4-5):(1-3):(20-25); the weight of concentrated sulfuric acid is 0.5-1.0‰ of the weight of N,N-dimethyldodecyl tertiary amine.

4. The method for preparing a low-foaming surfactant according to claim 1 or 2, characterized in that: in, The mass ratio of ethylene oxide to propylene oxide is 1:3-5; the mass ratio of propylene glycol to propylene oxide is 1:1; the alkali catalyst is sodium hydroxide or potassium hydroxide, and the added amount thereof is 0.1-0.5‰ of the weight of propylene glycol.

5. A cleaning agent, characterized in that: The cleaning agent includes a low-foaming surfactant prepared by the preparation method of claim 1 or a low-foaming surfactant prepared by the preparation method of claim 2.

Citation Information

Patent Citations

  • A kind of low-foaming polyether type surfactant and its synthetic method

    CN104324655B

  • Low-foam environment-friendly washing surfactant

    CN108211985A

  • Dehydroabietyl glycidyl ether grafted water-soluble hydroxypropyl chitosan and preparation method thereof

    CN111171180A